Coordination-induced radical generation: selective hydrogen atom abstraction via controlled Ti-C σ-bond homolysis - Mörsdorf, Jean-Marc; Ballmann, Joachim (Journal of the American Chemical Society, 2023)
A method for the generation of transient alkyl radicals via homolytic Ti-C bond cleavage was developed by employing a tailor-made organotitanium half-cage complex. In contrast to established metal-mediated radical initiation protocols via thermal or photochemical M-C σ-bond homolysis, radical formation is triggered solely by coordination of a solvent molecule (thf) to a titanium(IV) center. During the reaction, the nonstabilized alkyl radical is formed along with a persistent titanium(III) metalloradical, thus taming the former transient radical (persistent radical effect). Radical coupling and hydrogen atom abstraction (HAT) reactions have been explored not only experimentally but also computationally and by means of kinetic analysis. Exploiting these findings led to the development of selective HAT transformations, for example, with 9,10-dihydroanthracene. Deuterium labeling studies using selectively deuterated alkyls and 9,10-dihydroanthracene-d4 confirmed a radical pathway, which was underpinned by developing a radical-radical cross-coupling reaction for transferring the alkyl radical to a stable Sn-centered radical. To set the stage for an application in organic synthesis, a 5-endo-trig radical cyclization based on our methodology was established, and a dihydroxylated sesquiterpene was thus prepared in high diastereomeric excess.
Gesehen am 03.05.2024